The European Parliament as the voice of the European citizens? Examining the European Parliament’s role as a representative of the European citizens in the 2019 elections - Roberto Baccarini (QOE-IJES, 2024)
The European Parliament is considered a solution to the democratic deficit because the citizens of the EU directly elect it. This article aims to examine the validity of this claim. Concerning representativeness, the focus is on the homogeneity of rules and procedures used for electing the members of the European Parliament (MEPs). This homogeneity is considered as necessary for the EP to represent the EU citizens. Thus, it aims to assess the impact of the United Kingdom's withdrawal from the European Union on the level of homogeneity of the rules used to conduct the 2019 European Parliament elections. This work claims that the European Parliament's role as representative of European Citizens is weakened by the consistent level of heterogeneity characterising the electoral rules used to elect it and that the withdrawal of the UK and the partial redistribution of seats simultaneously increased and decreased the level of homogeneity of the rules used to elect the MEPs.